1989
DOI: 10.1093/nar/17.21.8553
|View full text |Cite
|
Sign up to set email alerts
|

Sequence, structure and evolution of the gene coding for sn-glycerol-3-phosphate dehydrogenase inDrosophila melanogaster

Abstract: We present the complete nucleotide and deduced amino acid sequence for the gene encoding Drosophila sn-glycerol-3-phosphate dehydrogenase. A transcription unit of 5kb was identified which is composed of eight protein encoding exons. Three classes of transcripts were shown to differ only in the 3'-end and to code for three protein isoforms each with a different C-terminal amino acid sequence. Each transcript is shown to arise through the differential expression of three isotype-specific exons at the 3'-end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…In Drosophila melanogaster, the Gpdh gene consists of eight exons and produces three isozymes by differential splicing of the last three exons (Cook et al, 1988;Bewley et al, 1989;von Kalm et al, 1989). We have analyzed in my laboratory 768 nucleotides from exons 3±6, coding for 256 amino acids, in 27 dipteran species (Kwiatowski et al, 1997;Barrio and Ayala, 1997).…”
Section: Evolution Of Glycerol-3-phosphate Dehydrogenasementioning
confidence: 99%
“…In Drosophila melanogaster, the Gpdh gene consists of eight exons and produces three isozymes by differential splicing of the last three exons (Cook et al, 1988;Bewley et al, 1989;von Kalm et al, 1989). We have analyzed in my laboratory 768 nucleotides from exons 3±6, coding for 256 amino acids, in 27 dipteran species (Kwiatowski et al, 1997;Barrio and Ayala, 1997).…”
Section: Evolution Of Glycerol-3-phosphate Dehydrogenasementioning
confidence: 99%
“…e Gpdh sequences are from the following studies: all ingroup species ϭ Barrio and Ayala (1997); MEL ϭ Bewley et al (1989). f Adh sequences are from the following studies: AMB ϭ Marfany and Gonzalez-Duarte (1991a); GUA and MAD ϭ Marfany and Gonzalez-Duarte (1993); SOB ϭ Marfany and Gonzalez-Duarte (1991b); TOL ϭ this study; MIR, PBO, and PER ϭ Schaeffer and Miller (1991); PSE ϭ Schaeffer and Miller (1992); MEL ϭ Kreitman (1983); YAK ϭ Ashburner (unpublished).…”
Section: Sequence Alignmentmentioning
confidence: 99%
“…The D. melanogaster Gpdh gene has eight exons, a single promoter and multiple polyadenylation signals (Bewley et al, 1989;von Kalm et al, 1989). There are two alternate 3 exons -exon 7 and exon 8.…”
Section: Introductionmentioning
confidence: 99%
“…The transcript containing exons 1 through to 6 codes for GPDH-3 and the transcript containing exons 1-6, skipping exon 7 and including exon 8 encodes GPDH-1 (Bewley et al, 1989;von Kalm et al, 1989). The product of translation of the transcript containing exons 1-7 has not been identified, but it has been suggested that this transcript might be coding for a novel isozyme GPDH-4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation